The Effect of Stress, Anxiety and Burnout Levels of Healthcare Professionals Caring for COVID-19 Patients on Their Quality of Life - Çelmeçe, Nuriye; Menekay, Mustafa (Frontiers in Psychology, 2020)
Background: The healthcare system is among the institutions operating under the most challenging conditions during the period of outbreaks like pandemic which affects the whole world and leads to deaths. During pandemics that affect the society in terms of socioeconomic and mental aspects, the mental health of healthcare teams, who undertake a heavy social and work load, is affected by this situation. Aim: This research was conducted with the aim of determining the effect of stress, anxiety, and burnout levels of healthcare professionals (doctors, nurses, healthcare assistants) caring for COVID-19 patients on their quality of life. Method: The sample of the study consisted of a total of 240 healthcare professionals, determined by random sampling method among the healthcare professionals working in pandemic hospitals in Tokat city center, Turkey. Perceived Stress Scale, Spielberger State-Trait Anxiety Inventory, Maslach Burnout Inventory and Quality of Life Scale were used in the study conducted in the relational screening model. Findings: While the stress, trait anxiety, and quality of life mean scores of healthcare professionals who were female, married and had children were higher than the other groups, high, moderate, negative, and positive correlations were found among all variables. Conclusion: The research concluded that the stress, anxiety, and burnout of healthcare workers caring for COVID-19 patients affected their quality of life.